Analisis Rasio Keuangan Dalam Mengukur Kinerja Keuangan Pada PT. XYZ - Desnita Layuk Allo; Elisabet Pali; Adriana M. Marampa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to find out the condition of financial performance at PT. XYZ Tbk. period 2020-2022. The data collection procedure for this study is secondary data taken from the first party. The data analysis technique for this study is quantitative using Liquidity Ratios (quick ratios and current ratios), Solvency Ratios (debt to asset ratio and debt to equity ratio), Profitability Ratio (ROE), Activity Ratio (total asset turnover). The results of this study are, in the calculation of the current ratio, quick ratio, debt to asset ratio, debt to equity ratio, ROE, the calculation results do not meet industry standards which results in the company's condition being in a bad condition, while the calculation of the asset turnover ratio has calculation results that exceed industry standards which means the value of asset turnover is in good condition.